Biotechnology operations : principles and practices - Roy, Michael J. (Michael Joseph) (Boca Raton : CRC Press, 2011)
'This book resulted from experiences gained working in biotechnology and while teaching a graduate course entitled Biotechnology Operations and offered to graduate students in the Master of Science (M.S.) in Biotechnology Program at the University of Wisconsin-Madison (http://www.ms-biotech.wisc.edu/ ). In this course we examine the undertaking of developing biotechnology products, focusing on the scientific and management skills of biomanufacturing, clinical trials, non-clinical studies, project management, quality assurance, quality control, and regulatory affairs. The course emphasizes both operational planning for success and integration of plans and efforts in these seven functional areas. The instructors realized from their experience in the biotechnology industry the great need to carefully plan and fully integrate biotechnology development projects. The course is taught in that manner and this book reflects that philosophy with the outcome is a practical guide for students and for those employed or interested in biotechnology'--Provided by publisher.
Includes bibliographical references (pages 383-386) and index.
Keywords: Biotechnology; Biotechnology industries; Biotechnological process control; Project management